Dynamics of Transformation of Islamic Education Through The Development of The Dsumberpucang People's - Evi Nurhalimah; Agus Maimun; Fauzan Zenrif; Ahmad Barizi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The education system at Islamic boarding schools is unique in that it emphasizes the close relationship between teachers and students. One of the characteristics of Islamic boarding schools is that they have strong religious values, have respected kyai, have mosques and dormitories in them. The teaching process uses lecture, discussion, memorization and demonstration methods. Currently, Islamic boarding schools also include the national school and madrasa curriculum and adopt e-learning to support the learning process. Islamic boarding school education has colored the education system under the Ministry of Religion. Several studies have been carried out regarding education such as Islamic boarding schools from a kyai's perspective, Salafi Islamic schools, the application of Islamic law in Islamic boarding schools. The role of Islamic boarding schools in managing good character, strategic management in Islamic boarding school education, the Salafi Islamic boarding school education system, the character of Islamic boarding school education.